UNIT 10F.2 Genetic Manipulation of Nocardia Species. Issue 1 (8th February 2016) - Dhakal, Dipesh; Kumar Jha, Amit; Pokhrel, Anaya; Shrestha, Anil; Sohng, Jae Kyung
Abstract : Nocardia spp. are aerobic, Gram‐positive, catalase positive, and non‐motile actinomycetes. They are associated with human infections. However, some species produce important natural products, degrade toxic chemicals, and are involved in biotransformation of valuable products. The lack of robust genetic tools has hindered detailed studies and advanced research. This unit describes the major genetic engineering approaches using Nocardia sp. CS682 as a prototype. These methods will certainly help in understanding the basis of their pathogenicity as well as biosynthetic and biotransforming abilities. It can be expected that knowledge of the biochemistry behind their pathogenicity will be crucial in developing effective treatment strategies. These genetic tools can be utilized to develop rational metabolic engineering approaches for crafting host strains with higher production or biotransformation ability. © 2016 by John Wiley & Sons, Inc.